The Most Segregated City in America" : City Planning and Civil Rights in Birmingham, 1920-1980 - Connerly, Charles E., 1946- (Book collections on Project MUSE., 2005)
"Connerly effectively uses Birmingham's history as an example to argue the importance of recognizing the link that exists between city planning and civil rights. His demonstration of how Birmingham's race-based planning legacy led to the confrontations that culminated in the city's struggle for civil rights provides a fresh lens on the history and future of urban planning, and its relation to race."--Jacket